Prevalence of Autoantibodies in Healthy Adults in Pakistani Population (Bangladesh Journal of Medical Science, 2016)
Introduction: Autoimmune phenomenon is attributed to a number of diseases which were once considered idiopathic. In humans, production of auto antibodies (a-Abs) against self-antigens is quite frequent but earlier their presence was associated with autoimmune diseases, however a-Abs have been documented in non-autoimmune disorders i.e. complicated pregnancy, cancer, stroke etc. In Pakistan, limited data is available on frequency of a-Abs, therefore this study was designed to determine serum level of antinuclear antibody (ANA), Rheumatoid factor (RF) and anti dsDNA antibodies in apparently healthy population.Materials and methods: After written informed consent, blood sample of 256 subjects was obtained by random sampling. Participants of established autoimmune diseases were excluded. Enzyme linked immunosorbent assay (ELISA) was used to determine ANA, RF and anti-dsDNA antibody. Categorical variables were compared by using c2 test. A p value